Coastal Ecosystems as Sources of Biofertilizers in Agriculture: From Genomics to Application in an Urban Orchard - Pajuelo, Eloísa; Arjona, Sandra; Rodríguez-Llorente, Ignacio D.; Mateos-Naranjo, Enrique; Redondo-Gómez, Susana; Merchán, Francisco; Navarro-Torre, Salvadora (Frontiers in Marine Science, 2021)
Pantoea agglomerans RSO7, a rhizobacterium previously isolated from Spartina maritima grown on metal polluted saltmarshes, had demonstrated good plant growth promoting activity for its host halophyte, but was never tested in crops. The aims of this study were: (1) testing PGP activity on a model plant (alfalfa) in vitro; (2) testing a bacterial consortium including RSO7 as biofertilizer in a pilot experiment in urban orchard; and (3) identifying the traits related to PGP activities. RSO7 was able to enhance alfalfa growth in vitro, particularly the root system, besides improving plant survival and protecting plants against fungal contamination. In addition, in a pilot experiment in urban orchard, a consortium of three bacteria including RSO7 was able to foster the growth and yield of several winter crops between 1.5 and 10 fold, depending on species. Moreover, the analysis of chlorophyll fluorescence revealed that photosynthesis was highly ameliorated. Genome analysis of RSO7 depicted the robustness of this bacterial strain which showed resilience to multiple stresses (heat, cold, UV radiation, several xenobiotics). Together with wide metabolic versatility, genes conferring resistance to oxidative stress were identified. Many genes involved in metal resistance (As, Cu, Ni, Co, Zn, Se, Te) and in tolerance toward high osmolality (production of a battery of osmoprotectans) were also found. Regarding plant growth promoting properties, traits for phosphate solubilization, synthesis of a battery of siderophores and production of IAA were detected. In addition, the bacterium has genes related to key processes in the rhizosphere including flagellar motility, chemotaxis, quorum sensing, biofilm formation, plant-bacteria dialog, and high competitiveness in the rhizosphere. Our results suggest the high potential of this bacterium as bioinoculant for an array of crops. However, the classification in biosecurity group 2 prevents its use according to current European regulation. Alternative formulations for the application of the bioinoculant are discussed.